Hereditary truncating mutations of DNA repair and other genes in BRCA1/BRCA2/PALB2-negatively tested breast cancer patients - Lhota, F; Zemankova, P; Kleiblova, P; Soukupova, J; Vocka, M; Stranecky, V; Janatova, M; Hartmannova, H; Hodanova, K; Kmoch, S; Kleibl, Z (Clinical genetics, 2016)
Hereditary breast cancer comprises a minor but clinically meaningful breast cancer (BC) subgroup. Mutations in the major BC-susceptibility genes are important prognostic and predictive markers; however, their carriers represent only 25% of high-risk BC patients. To further characterize variants influencing BC risk, we performed SOLiD sequencing of 581 genes in 325 BC patients (negatively tested in previous BRCA1/BRCA2/PALB2 analyses). In 105 (32%) patients, we identified and confirmed 127 truncating variants (89 unique; nonsense, frameshift indels, and splice site), 19 patients harbored more than one truncation. Forty-six (36 unique) truncating variants in 25 DNA repair genes were found in 41 (12%) patients, including 16 variants in the Fanconi anemia (FA) genes. The most frequent variant in FA genes was c.1096_1099dupATTA in FANCL that also show a borderline association with increased BC risk in subsequent analysis of enlarged groups of BC patients and controls. Another 81 (53 unique) truncating variants were identified in 48 non-DNA repair genes in 74 patients (23%) including 16 patients carrying variants in genes coding proteins of estrogen metabolism/signaling. Our results highlight the importance of mutations in the FA genes' family, and indicate that estrogen metabolism genes may reveal a novel candidate genetic component for BC susceptibility.
Keywords: senioři; jaderné proteiny; Breast Neoplasms; senioři nad 80 let; Fanconi Anemia Complementation Group N Protein; hereditary breast cancer; protein BRCA2; Nuclear Proteins; genetic predisposition testing; DNA Mutational Analysis; Middle Aged; mutace; protein FANCL; high-throughput nucleotide sequencing; mutační analýza DNA; Aged, 80 and over; ženské pohlaví; nádorové supresorové proteiny; Mutation; DNA repair; Humans; FANCL; oprava DNA; Tumor Suppressor Proteins; lidé středního věku; BRCA2 Protein; SOLiD next-generation sequencing; nádory prsu; Fanconi Anemia Complementation Group L Protein; BRCA1 Protein; protein FANCN; protein BRCA1; DNA Repair; Female; Aged; lidé; sequencing panel